Pengembangan Keterampilan Bercocok Tanam Teknik Vertikultur untuk Santri Sebagai Aktivitas Produktif di Lahan Sempit - Hermanto, Agus; Shidqia, Dzu Dilla; Fadillah, Nurul; Ntoma, Vanesha Naifah (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
Limited land to be utilized in providing more benefits for life such as planting in plant cultivation, as something that is common in big cities. The purpose of this service activity is to share solutions to the problem of narrow yards at Pondok Tahfiz Al-Firdaus. The method used is participatory action research in the form of socialisation about verticulture and training activities for planting plants using verticulture techniques. The socialization stage provides material on verticulture overview, equipment and materials, planting media and planting and maintenance methods. In the training, activities were carried out in the form of preparation and practice of planting verticulture methods. The results of this service activity showed an increase in the understanding of the santri as participants in the activity about verticulture as a way of planting on narrow land. The seriousness and success of the participants in practicing verticulture. By directly carrying out verticulture planting activities, it becomes a starting point that this service activity is successful.